Jak nas czytają za granicą? Ankieta - Grigorowa, Margreta (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
Answering questions about the functioning of Polish literature and culture in university circles in her country, Margreta Grigorowa provides detailed and precise information about the reception, impact and institutional setting of our native literature in Bulgaria (she lists important centers promoting Polish culture and magazines specializing in this subject, as well as the names of translators and the scope of their translation activity). The researcher also points to the general principles of reading Polish writers (from the Old Polish era, through Romanticism to modern times), emphasizing that their works are read primarily through the prism of the Polish history, in religious and philosophical context. In addition, the idea of compensation plays an important role in the reception of Polish art in Bulgaria as Polish literature attracts the attention of the Bulgarian readership by its otherness and ability to confront different experiences and mentalities.